Consumer obligatory practices, knowledge and behaviour towards halal certification in Malaysia - Mohd Amin, Al ‘Uyuna; Zakaria, Zalina; Abdul Rahim, Alina; Abdul Rahim, Norhayati Rafida (2019)
Every Muslim must consume halal products, therefore fulfilling a halal lifestyle which is a mandatory requirement for practising Muslim. Consumption of halal products is an obligation need for the global Muslim. There are several races from various ethnicities, including Malays, Chinese, Indians and others who are not necessarily Muslims; therefore applications of halal certification from Malaysia manufacturers are stated as voluntary. According to statistics from the Department of Statistics of Malaysia as of up to June 2019, 69.3% are Muslim, 22.8% Chinese, 6.9% Indians and 1.0% comprise of others. This study will examine whether voluntary Malaysian halal certification is still relevant today or need to be considered to ensure that the Malaysians have access to halal resources. In order to obtain information on this subject, data collection by questionnaire was conducted during a national halal food seminar organized by USIM on 28th September 2019. The target audience is young people aged between 18-30. The feedback from the younger generation is needed in order to raise awareness about halal. The results of this study show that the Muslim’s millennials are educated from Islamic school background; the level of halal awareness was at sufficient level. Indirectly, it shows that Muslim students have a broad knowledge of the concept of halalness, and the determination to obtain halal-certified food was considered fair.